Study on the hydrocyclonic separation of waste plastics with different density. (November 2015) - Yuan, H.; Fu, S.; Tan, W.; He, J.; Wu, K.
Highlights: PET/PVC mixtures were effectively separated with their purity being all above 90%. The relationship between the separating efficiency and pressure drop has been tested. The relationship between the separating efficiency and split ratio was obtained. Abstract: The recycling of waste plastics is an important aspect in the recycling of solid waste. Based on the difference in density, PET and PVC particles was separated with help of the centrifugal sedimentation and shearing dispersion in a hydrocyclone. Through tests and CFD simulation, the relationship between the separating efficiency and pressure drop and split ratio has been investigated. Test results show that the Newton efficiency can reach above 80%, i.e. the purity of PVC could reach 93.2% while the purity of PET could reach 94.5%.